2019
DOI: 10.1016/j.resuscitation.2018.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mild hypercapnia on outcome and histological injury in a porcine post cardiac arrest model

Abstract: Aim of the study: To evaluate in an established porcine post cardiac arrest model the effect of a mild hypercapnic ventilatory strategy on outcome. Methods: The left anterior descending coronary artery was occluded in 14 pigs and ventricular fibrillation induced and left untreated for 12 min. Cardiopulmonary resuscitation was performed for 5 min prior to defibrillation. After resuscitation, pigs were assigned to either normocapnic (end-tidal carbon dioxide (EtCO 2) target: 35-40 mmHg) or hypercapnic ventilatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…In our study, there was a slightly increased MAP and ICP in mild hypercapnia group. The result of a higher MAP in the mild hypercapnic animals was consistent with previous studies [10,33]. However, there were studies suggesting no association between hypercapnia and MAP [13,34].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In our study, there was a slightly increased MAP and ICP in mild hypercapnia group. The result of a higher MAP in the mild hypercapnic animals was consistent with previous studies [10,33]. However, there were studies suggesting no association between hypercapnia and MAP [13,34].…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies showed asphyxial CA model causes more severe cerebral metabolism injuries and ischemic brain injury after asphyxial CA appears more severe and more widespread than VF model of the same duration [36,37]. Second, we defined mild hypercapnia as EtCO 2 between 45 and 50 mmHg based on previously published studies [10], which may be arbitrary, since the target EtCO 2 levels associated with potential benefit or harm are unknown. Third, we only assessed two different levels of EtCO 2 for a period of 12 h. Fourth, Pbto 2 is a focal measure, which could not represent the global monitor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations